Biodiversity - Gonçalves, M. (Open Schools Journal for Open Science, 2020)
Our school is surrounded by tall buildings and cement and has little green areas, but even so, we managed to find a place to build a small bio-vegetable garden, an orchard of native trees, and a vineyard. Students also increased the number of flowerbeds and built nests for insectivorous birds, a pond for frogs, spots with aromatic plants, as well as a hotel for pollinating insects. Students are also sowing wild plants to increase local biodiversity.